Ø§Ù„Ø±Ø¯ Ø¹Ù„Ù‰ Ø´Ø¨Ù‡Ø§Øª ÙˆØ§Ø¹ØªØ±Ø§Ø¶Ø§Øª Ø§Ù„Ù…Ø³ØªØ´Ø±Ù‚ÙŠÙ† Ø¹Ù„Ù‰ ØØ¬ÙŠØ© Ø§Ù„Ø³Ù†Ø© (Ø¯Ø±Ø§Ø³Ø© ØªØÙ„ÙŠÙ„ÙŠØ© ÙˆØµÙÙŠØ© Ø¹Ù„Ù‰ Ø§Ù„Ø£ØØ§Ø¯ÙŠØ« Ø§Ù„ÙˆØ§Ø±Ø¯Ø© ÙÙ‰ ÙƒØªØ§Ø¨Ø© Ø§Ù„ØØ¯ÙŠØ«) - Misbakhudin Misbakhudin (Religia, 2009)
Different interpretation of prophetic narrative on the prohibition and allowance of hadith writing had brought about negative perception of Orientalist that leaded to a conclusion to refuse using hadith as hujjah. Ignaz Goldziher, Hungarian Jewish, thought that most hadith could not be warranted, its originality (or counterfeit), therefore, they could not be information sources of the early history of Islam. According to him, hadith is more meant as a reflection of many currents interaction and conflict, and latter tendency in mature period, rather than a historical document of the early development of Islam. It means, to him, hadith is a product of Islamic community that lived several centuries after the prophet Mohammed, not originally from him. This opinion had been opposed by a number of Islamic experts, like Syaikh Musthafa as-Siba’I, and Abd al-Ghani Abd al-Khaliq.